http://ezaccess.library.uitm.edu.my/login?url=http://services.igi-global.com/resolvedoi/resolve.aspx?doi=10.4018/978-1-4666-0924-2 - Colomo-Palacios, Ricardo, 1973- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"This book offers the latest managerial trends within the field of information technology management, offering a broad variety of case studies, best practices, methodologies, and research within the field of information technology management"--Provided by publisher.